A Study of Voluntary Regulation Components in Children of the First Grade - Savina E. A.; Logvinova A. E. (Moscow State University of Psychology and Education, 2015)
The present study examines the components of voluntary regulation in children of the first grade. Children (N = 82) were asked to perform tasks, measuring the ability of inhibition of verbal behavior (tests "yes-no", "day-night"), working and short-term memory, knowledge of the rules of behavior in the classroom, the ability to follow a visual pattern ("Butterfly") and verbal instruction ("Graphic dictation"). It has been found that girls have a higher regulation of verbal behavior than boys. It is shown that the working memory is an essential component of any regulation: for example, children with higher working memory abilities also showed a higher level of inhibition and the ability to follow the pattern and instructions. The regulation of verbal behavior is important both to follow verbal and visual pattern instructions and to control interference. The number of rules of conduct, provided by these children, was positively associated with the test that measures the ability to inhibit verbal behavior: "day-night". The findings indicate the need for the formation in children of speech mediation activities and methods of working memory